Assessment of prospects using the latest technology stabilization of beverage - Piddubny, Vladimir; Sova, Mykola; Shevchenko, Oleksandr (My University, 2013)
The article presents information related to microbiological stabilization of carbonated and non-carbonated beverages, including high energy value from raw materials of plant origin due to the choice of parameters and modes of heat treatment.
Keywords: кафедра мехатроніки та пакувальної техніки; кафедра процесів і апаратів харчових виробництв; stabilization; pasteurization; microbial cells; стабілізація; пастеризація; мікробні клітини